2007
DOI: 10.1021/ol070813t
|View full text |Cite
|
Sign up to set email alerts
|

Samarium Triflate-Catalyzed Halogen-Promoted Friedel−Crafts Alkylation with Alkenes

Abstract: A versatile and efficient halogen-promoted highly regio- and stereoselective Friedel-Crafts (F-C) alkylation with alkenes has been developed with use of easily available and inexpensive NBS or I2 as the efficient halogen sources. Lewis acids, in particular metal triflates, are found to be effective catalysts for this halogen-promoted F-C alkylation. Among these, Sm(OTf)3 was the best catalyst. Electron-rich arenes smoothly underwent F-C alkylation with a variety of alkenes including alpha,beta-unsaturated carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…To date, only one solitary report on intermolecular Friedel–Crafts alkylation with alkenes via in situ generated three‐membered halonium ion intermediates using inexpensive NBS/or I 2 as halogen sources has been published. In this report, it was observed that the metal triflates‐based Lewis acids were able to activate NBS and, among them, Sm(OTf) 3 was found to be the best in terms of chemical yield.…”
Section: Reaction Classessupporting
confidence: 70%
“…To date, only one solitary report on intermolecular Friedel–Crafts alkylation with alkenes via in situ generated three‐membered halonium ion intermediates using inexpensive NBS/or I 2 as halogen sources has been published. In this report, it was observed that the metal triflates‐based Lewis acids were able to activate NBS and, among them, Sm(OTf) 3 was found to be the best in terms of chemical yield.…”
Section: Reaction Classessupporting
confidence: 70%
“…In contrast, a single report on the intermolecular version of Friedel-Crafts alkylation triggered by "haliranium ion" intermediate has been reported by Hajra Group (Scheme 1c). [13] In other means, judging by the recent development, the Friedel-Crafts reactions promoted by the unique fluorinated solvent [TFE (2,2,2-trifluoroethanol)/HFIP (1,1,1,3,3,3-hexafluoro-2-propanol)] have gained a substantial interest. [14] In HFIP, Mayr, [15] Paquin, [16] Khaledi, [17] Xiao [18] and Moran [19] groups reported the Friedel-Crafts benzylations to access 1,1-diarylalkanes or Polyarylated alkanes without using any externally added catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…A straightforward strategy for the synthesis of these subunits could be a regioselective F‐C reaction of easily accessible spiro‐epoxyoxindole with heteroarenes and arenes. Our continuous research interest in exploring the reactivity of three membered reactive intermediates led us to envisage the Lewis acid catalysed F‐C reaction of spiro‐epoxyoxindoles with arenes as well as heteroarenes. After the affirmative presumption, recently, we have successfully reported the Lewis‐acid catalysed efficient F‐C reaction of spiro‐epoxyoxindoles with indoles and arenes to obtain both the functionalities (Scheme ) …”
Section: Introductionmentioning
confidence: 99%